The Palgrave handbook of transformational giftedness for education - Sternberg, Robert J.; Ambrose, Donald; Karami, Sareh (Springer eBook Collection, 2022)
Chapter 1: Discovering and Dismantling Enormous Barriers Hindering the Transition from Transactional to Transformational Giftedness; Don Ambrose - Rider University -- Chapter 2: The Beautiful Risk of Moving Toward Pedagogies of the Possible.; Ronald A. Beghetto and Vlad P. Glăveanu - Arizona State University and the University of Bergen -- Chapter 3: Respecting the Invisible: Transactional and Transformational Approaches to Giftedness; Dowon Choi and James C. Kaufman - Florida State University and Arizona University.-Chapter 4: From I to We: The Three C’s Conception of Gifted Education; Aakash A. Chowkase and Sujala Watve - Purdue University and Jnana Prabodhini’s Institute of Psychology -- Chapter 5 :A Catalyst for Change: Improving the World through Talent Development; Jennifer Riedl Cross and Tracy L. Cross - College of William & Mary -- Chapter 6: Ten Changes that Will Render Gifted Education Transformational; David Yun Dai - University at Albany, State University of New York -- Chapter 7: Promoting Transformational Giftedness Through Service Learning; Ophélie Allyssa Desmet - Valdosta State University -- Chapter 8: Fairminded Critical Thinking and Depth of Knowledge as Essential to Gifted Education Programs that Advance the Common Good; Linda Elder - Foundation for Critical Thinking.-Chapter 9: Be Prepared for the Complexities of the 21st Century!; Joachim Funke - Heidelberg University -- Chapter 10: Addressing Access, Equity, and Missingness to Transform Gifted Education; Marcia Gentry - Purdue University -- Chapter 11: Through the Dąbrowski Lens: Wisdom, Transformational Giftedness, and the Personality Ideal; Amanda J. Harper - University of Tasmania -- Chapter 12: Evidence of Transformational Giftedness in the Profoundly Gifted When We Use the "Integral Practice the Gifted™" Model; P. Susan Jackson - Daimon Institute for the Highly Gifted Inc -- Chapter 13: Starting Over: An Iranian Conception of Giftedness and How It Can Transform Societies and the World.; Sareh Karami and Mehdi Ghahremani - Mississippi State University -- Chapter 14: Transformational Education as a Work in Process: Insights from Transformationally Gifted Adults; Lori Lutz - The Roeper Institute -- Chapter 15: The Rainbow Revolution: Empowering Gifted LGBTQ+ Learners for Transformative Action; Andres Parra-Martinez and Alena R. Treat - Purdue University and Upper Iowa University -- Chapter 16: Transformational Giftedness: Using SEM Pedagogy to Create Future Leaders and Change Agents Dedicated to Service, Social Responsibility, and Using Their Talents to Improve the Planet; Sally M. Reis and Joseph S. Renzulli - University of Connecticut -- Chapter 17: Equity, Social Justice and Transformational Giftedness - A Gifted Academy in a Vulnerable Community; Renu Singh and Bharath Sriraman - Maryvale Gifted & Talented Academy and University of Montana - Missoula -- Chapter 18: Transfrmational Giftedness: Who’s Got It and Who Does Not; Robert J. Sternberg - Cornell University -- Chapter 19: Channeling Gifted Abilities into Transformative Creative Productivity; Rena F. Subotnik, Paula Olszewski-Kubilius, and Frank C. Worrell - American Psychological Association, Northwestern University, University of California, Berkeley -- Chapter 20: Educating Ethical Minds in Gifted Education; Kirsi Tirri - University of Helsinki.-Chapter 21: Redefining Human Talents: Gifted Education in the Age of Smart Machines; Yong Zhao, James Basham, and Jason Travers - Melbourne Graduate School of Education, University of Kansas, Temple University -- Chapter 22: In Conclusion: Where We Currently Stand in the March Toward Transformational Giftedness.